Implementasi metode NIOSH dan analisa QEC pada alat potong ranting - Zufri Hasrudy Siregar; Margie Subahagia Ningsih (Universitas Mercu Buana, 2019)
This research is the design of new technology which is simple by engineering hydraulic system and principles of hand grip which functions as adjustable twig clipper that is ergonomic, with the normal length of 1.5 meters, maximum length of 3 meters., weight of 2.8 kg, the length of grip range of 94 mm and handlebar diameter of 52 mm. This research used the method of ergonomic analysis to identify the suitability of the device with human by taking 95 percentile. From the findings, the hand grip diameter obtained is 54, 29 mm while the hand palm width is 97.87 mm, and the maximum pressure required to cut the branch is 522.29 kg/cm2 with a diameter of 1 cm that is for the type of clove twig. In addition, from the NIOSH analysis, it is obtained that the required weight is 4.89 Kg while from the QEC method, the highest score percentage is 47.62. This means that it is necessary to improve the equipment in the future. In order to prevent tiredness, the suggested working duration is 8.40 minutes and 7.14 minutes for resting time. From the results of research, it can be concluded that this device still needs to be improved in the future. In addition, the usage time is quite short and it is only functioned for harvesting clove and harvesting other similar with maximum diameter of 1 cm.